(Un)distorted stabilisers in the handlebody group. Issue 2 (24th March 2021) - Hensel, Sebastian
Abstract: We study geometric properties of stabilisers in the handlebody group. We find that stabilisers of meridians are undistorted, while stabilisers of primitive curves or annuli are exponentially distorted for large enough genus.